Differential effects of two NMDA receptor antagonists on cognitive–behavioral performance in young nonhuman primates II - Popke, E.J; Allen, R.R; Pearson, E.C; Hammond, T.G; Paule, M.G (Neurotoxicology and teratology, 2001)
The present experiment examined the effects of chronic exposure to remacemide (an NMDA antagonist that also blocks fast sodium channels) or MK-801 (which blocks NMDA receptors more selectively) on the acquisition of color and position discrimination and short-term memory behavior in juvenile rhesus monkeys. Throughout the 2-year dosing period, a conditioned position responding (CPR) task was used to assess color and position discrimination and a delayed matching-to-sample (DMTS) task was used to assess memory. Chronic exposure to high doses of either drug delayed the acquisition of accurate color and position discrimination without altering response rates. In the case of MK-801, these effects abated within 6 months of the start of treatment. In the case of remacemide, the effects persisted for 17 months of dosing. Neither compound significantly altered performance of the short-term memory task at any time point or at any dose tested. The fact that the effects of remacemide on behavioral performance were more persistent than those seen for MK-801 suggests that tolerance may develop to the behavioral effects of MK-801, which does not develop to the effects of remacemide. Alternatively, these results may suggest that the concurrent antagonism of NMDA receptors and fast sodium channels may have more profound consequences for behavior than does the antagonism of NMDA receptors alone.